Shallow or deep water for adjustment? A study in children aged 3 to 6 years - Scurati, R.; Michielon, G.; Longo, S.; Invernizzi, P. L. (Biomechanics and Medicine in Swimming XI, 2010)
In a learn-to-swim programme, the question of what is the best environmental condition for aquatic adjustment. The choice could depend on the depth of the swimming facilities or on the swimming teaching methodology. This study aimed to compare the outcomes of water adjustment carried out in deep or shallow water in 3 to 6 year old children. Children practicing the learning programme in deep water obtained a higher mean score, but not significantly different than the children having a shallow water adjustment programme. The depth of the swimming pool seems to not significantly affect the results. Children can approach guided experiences equally either in shallow or deep water to learn the swimming basic skills and independence in the water, with no differences in the rate of acquisition or in the quality of the skills.